HUBUNGAN KARAKTER FENOTIPIK DAN HASIL BIJI PLASMA NUTFAH KACANG TUNGGAK [Vigna unguiculata (L.) Walp.] MENURUT ANALISIS LINTASAN - Mastur, Mastur; Setyowati, Mamik; Susilowati, Dwi N. (BERITA BIOLOGI, 2018)
Selection of high quality seedling through plant breeding activity can be conducted using yielded seeds, but usually it produces a low heritability. Therefore, this study was aimed to examine and analize several secondary phenotypic characters of 115 cowpea germ plasms in relation to seed yield. Relationship between secondary characters and seed yield was analyzed using path analysis. The result of path analysis showed that the number of cluster and the number of pod exhibited direct and significant effect to the seed yield of cowpea. Therefore, number of cluster and number of pod are necessary to be included as the selection criteria for breeding programme to produce high quality cowpea seedling with high yield.